WATER REPELLENT THIN FILM POLYMER COMPOSITES WITH RED MUD PARTICLES AS TEXTURE FORMING AGENTS - МИРОНЮК, О. В.; БАКЛАН, Д. В.; ЛІ, Ч. (Technologies and Engineering, 2023)
Purpose. To confirm the possibility of manufacturing thin-layer water-repellent coatings based on red mud particles. Methodology. In this work, red mud was used to create a microtexture. The decontamination process was carried out at a temperature of 950 °C to lower the pH. Stearic acid, methyltriethoxysilane, and octyltriethoxysilane were used as hydrophobic agents. Styrene-butyl-acrylate polymer was used as a polymeric binder. A laser particle analyzer was used to obtain particle size data. An optical microscope and a digital camera were used to take photographs of the sample surface. Infrared spectroscopy was used to confirm the modification of the red mud using KBr pellets as an inert carrier. The water contact angles were measured by the sessile drop method using a goniometer and a digital camera. The determination of contact angles for hydrophilic materials was performed by the Washburn thin-walled capillary impregnation method. Findings. The paper considers one of the options for utilizing red mud to obtain a micro-sized base for water-repellent coatings. It is shown that the largest water contact angle is 143° and is achieved by using stearic acid as a modifier in thin-film composites depleted of binder. It has been established that red mud can be considered as a suitable basis for obtaining hierarchical systems with the prospect of achieving a hydrophobic state along with conventional dispersed fillers. Originality. It is shown for the first time that coatings with high water-repellent properties can be obtained on the basis of red mud particles. Practical value. The method of treatment of aluminum production waste - red mud, which consists in sintering, dispersing and hydrophobization, and the corresponding composition of the organic-mineral coating based on prepared particles, which has a uniform water-repellent surface, have been developed.